Aplikasi Point Of Sale Berbasis Web Dengan Metode Scan Barcode (Studi Kasus : K¬afe Dapur Pisang) - Waren Asmara Sedi; Bagas Setiyaki Wicaksono (CV. Multi Kreasi Media, 2022)
Point Of Sale or abbreviated (POS) can be translated freely as a cashier system, is a sales-oriented activity that occurs in the retail/cafe business sector. This POS becomes very valuable because POS is a terminal that receives money from customers. For business owners, cash income is a simple indicator of business income. One of the website-based application systems needed at the Banana Kitchen Cafe is the Point Of Sale, because at the Banana Kitchen Cafe the cashier system still uses the manual method. A system with a high level of dynamics, while the budget and available development time are very, very limited. Data collection methods in this study are literature study, interviews, observation, and data analysis. The design system development method used by researchers to design a Point Of Sale Application System with a waterfall model defined by Pressman is a classical model in forming software with sequential properties. As a result, this cafe can make buying and selling transactions digitally and the buying and selling transactions look more structured and simple.